PERAN PEMBELAJARAN IMMERSIVE UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA: A LITERATUR REVIEW - Nando, Fery; Nurfina Istiqomah, Hanin Fathan; Muhammad Arbi; Istiqomah; Rifky Aditya Ramadhan; Banu Widiasmara (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Creative thinking skills are one of the essential competencies that students must master to face the challenges of the Industrial Revolution 4.0 era, characterized by the rapid development of technology and automation. Immersive learning, which utilizes technologies such as virtual reality (VR) and augmented reality (AR), is considered effective in enhancing students' creative thinking skills. This article aims to review the literature on the role of immersive learning in improving students' creative thinking skills through five main stages: topic selection, literature search, literature selection, analysis and synthesis, and organizing the writing. The literature review findings show that immersive technology facilitates students to learn in interactive and multidimensional environments. This condition allows students to think critically, generate new ideas, and solve problems innovatively. Furthermore, the literature review results indicate that immersive learning plays an important role in enhancing the aspects of creative thinking skills, including fluency, flexibility, originality, and elaboration, through its interactive features and environments that provide various simulations